40% Glucose Gel for the Treatment of Asymptomatic Neonatal Hypoglycemia. (October 2021) - Gibson, Brandi L.; Carter, Brigit M.; LeDuff, Lawrence D.; Wallace, Angela
Abstract : Background: The Mother Infant Care Center at Fort Belvoir Community Hospital (FBCH) recently revised its asymptotic neonatal hypoglycemia (ANH) protocol and adopted 40% glucose gel into its treatment pathway. The previous protocol used infant formula as the primary intervention. Purpose: To evaluate the effectiveness of 40% glucose gel on exclusive human milk diet rates, time on protocol, level II Special Care Nursery (SCN) admission rates, length of stay (LOS), and total hospital costs for newborns with ANH at FBCH. Methods: Infants with ANH were treated with 40% glucose gel (n = 35) and compared with a historical group of infants with ANH (n = 29) who were treated with formula. Results: Exclusive human milk diet rates increased by 33.6%. The mean time on protocol dropped by 1.13 hours. The SCN admission rates dropped by 2.4% in the postimplementation group. The mean LOS was more than 12 hours less in the postimplementation group. The mean total cost per patient was 1190.60 lower after implementation of 40% glucose gel. Implications for Practice: The use of 40% glucose gel is a patient-focused, less-invasive, and cost-effective treatment of ANH. Implications for Research: More studies are needed to better define neonatal hypoglycemia. The use of 40% glucose gel is safe for use in infants with ANH; however, more studies are needed to examine its comprehensive benefits.